Liberdade e movimento em Thomas Hobbes - Machado, Evandro José (2011)
In the absence of external impediments the free action of men, what kind of society exist? Is it true that men get together in society as a pure gratuity? A strong and sovereign power, able to handle all the needs and passions in right? If men have always sought to be free, why an organized able to control them? Thomas Hobbes, on the basis of similar interjections, sought answers in context, fully imbued with innovative scientific ideas. This scientific process emerged in an attempt to legitimize the Copernican system of the universe, which was based on mathematically study the movements of physical bodies. As a result, there was a sharp break with traditional cosmofisica and the emphasis focused on the relation of cause and effect of physical phenomena. Hobbes applied this new methodology in political philosophy and said that the world is a joining of bodies in motion. This was a mechanical man, and also extended to the state, that as perfect machines can have their movements controlled and known by science that made them the object of his study. While the state was described as an artificial man, who mimics the natural man, the mechanics of man was drafted in a way analogous to a clock. However, Hobbes showed that men, when inserted in the natural state, they acted according to his own passions and always looking for its own sake: the principle of benefit. A sphere improper to preserve life. Because of right reason, men came to the conclusion that the institution of the Leviathan is the most effective output, so that the pleasant life and peace are guaranteed. Based on the scenario, the present paper, which is entitled Freedom and Movement in Thomas Hobbes , seeks to demonstrate the application of the movement a legacy of science the concept of freedom, understood and disseminated so far as freedom of the will and rational beings, and therefore, a metaphysical attribute. From Hobbes, liberty is merely applied to the whole body and body, rational or not, since it is moving. It is this sense that the hobbesian definition of freedom, the absence of external restraint to the movement, the truth wins and becomes incompatible with the natural order, which is to keep the peace. In order to preserve the vital movement and a comfortable life, men, therefore, limit the freedom and start living under civil law.